Explaining national differences in education-work transitions : twenty years of research on transition systems - Raffe, David [Verfasser] (My University, 2014)
"In the 1980s and 1990s the study of education-work transitions took a comparative turn. Researchers sought to identify national differences in transition processes and outcomes and explain them in terms of institutional characteristics of national 'transition systems'. This was an ambitious aim because it required the study of transitions to develop as a field of 'macro' social-science research, while continuing also to use theories, techniques of analysis and data associated with 'micro' research. This paper reviews the progress of transition-system research over the past 20 years. It describes the development of the research field and how it has been shaped by its theoretical origins, the political context, the availability of data and the organisation of research. The research has made significant if uneven progress towards explaining national differences in transitions; its achievements appear more significant when viewed from a perspective which emphasises the case-oriented rather than variables-oriented aims of comparative research." (Authors' abstract, BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; I 2.2 Europa; Vergleichende Berufsbildungsforschung; Arbeitsmarktforschung; Berufseinmündung; Zweite Schwelle; Internationaler Vergleich; Europa